2020
DOI: 10.1155/2020/6904517
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Sulfide as Cathode Materials for Lithium-Ion Batteries: Advances and Challenges

Abstract: Due to the ever-growing demand for high-density energy storage devices, lithium-ion batteries with a high-capacity cathode and anode are thought to be the next-generation batteries for their high energy density. Lithium sulfide (Li 2 S) is considered the promising cathode material for its high theoretical capacity, high melting point, affordable volume expansion, and lithium composition. is review summarizes the activation and lithium storage mechanism of Li 2 S cathodes. e design strategies in improving the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 79 publications
(121 reference statements)
1
21
0
Order By: Relevance
“…Since the incorporated In 2 S 3 achieves a certain level (x = 0.02), the available free space for Li + passage would be lessened, which may reduce ionic conductivity. The σ Li+ of the electrolytes was measured by the equation given below (2) Moreover, the activation energy (E a ) of Li 7 P 3 S 11 -xIn 2 S 3 (x = 0, 0.005, 0.01, and 0.02) electrolytes can be calculated from the slope of the Arrhenius equation (3) Here, σ, A T, and k represent lithium ionic conductivity, preexponential factor, absolute temperature, and Boltzmann constant. Interestingly, it is observed that Li 6.93 P 2.97 In 0.02 S 10.92 presents the lowest E a of 21.2 kJ mol −1 among the electrolytes, while the pristine Li 7 P 3 S 11 electrolyte offers the highest E a of 25.9 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the incorporated In 2 S 3 achieves a certain level (x = 0.02), the available free space for Li + passage would be lessened, which may reduce ionic conductivity. The σ Li+ of the electrolytes was measured by the equation given below (2) Moreover, the activation energy (E a ) of Li 7 P 3 S 11 -xIn 2 S 3 (x = 0, 0.005, 0.01, and 0.02) electrolytes can be calculated from the slope of the Arrhenius equation (3) Here, σ, A T, and k represent lithium ionic conductivity, preexponential factor, absolute temperature, and Boltzmann constant. Interestingly, it is observed that Li 6.93 P 2.97 In 0.02 S 10.92 presents the lowest E a of 21.2 kJ mol −1 among the electrolytes, while the pristine Li 7 P 3 S 11 electrolyte offers the highest E a of 25.9 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, rechargeable batteries or fuel cells are promising next-generation battery technologies . Among battery technologies, lithium–sulfur (Li/S) batteries with high energy density are acknowledged as one of the most promising candidates to ensure the power starting from low to heavy locomotives. However, the commercialization of Li/S cells is yet restricted by some problems, for example, shuttling of polysulfide intermediates (Li 2 S x : 4 ≤ x ≤ 8) declines the cyclic performance and Coulombic efficiency of the Li/S cells badly.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 a–c exhibit the galvanostatic charge-discharge profiles of Li 2 Se-LiTiO 2 , Li 2 Se and LiTiO 2 cathodes. A noticeable overpotential (2.93 V) can be observed in Li 2 Se cathode during the first charge profile, which is related to the obstruction of Li + extraction from crystalline Li 2 Se and the formation of a new interface [ 40 ]. Impressively, the overpotential of Li 2 Se-LiTiO 2 cathode is dramatically diminished to only 2.15 V. It is probably attributed to the presence of oxygen vacancies, where Ti 4+ is converted to Ti 3+ in the synthesis process [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar tendency can also be found in other types of Li-rich sulfides/selenides. 46 The strongest peak of (001) reflection of Na-doped LiNaFeS 2 material is highlighted in Fig. 2c.…”
Section: Key Challenges For Lithium-rich Sulfides/selenidesmentioning
confidence: 95%